The RNA polymerase of influenza a virus is stabilized by interaction with its viral RNA promoter. - Brownlee, G; Sharps, J (2002)
The RNA polymerase of the influenza virus is responsible for the transcription and replication of the segmented RNA viral genome during infection of host cells. Polymerase function is known to be strictly dependent on interaction with its RNA promoter, but no attempts to investigate whether the virion RNA (vRNA) promoter stabilizes the polymerase have been reported previously. Here we tested whether the vRNA promoter protects the polymerase against heat inactivation. We prepared partially purified recombinant influenza A virus RNA polymerase, in the absence of influenza virus vRNA promoter sequences, by transient transfection of expression plasmids into human kidney 293T cells. The polymerase was found to be heat labile at 40 degrees C in the absence of added vRNA. However, it was protected from heat inactivation if both the 5' and 3' strands of the vRNA promoter were present. By using the ability of vRNA to protect the enzyme against heat inactivation, we established a novel assay, in conjunction with a mutagenic approach, that was used to test the secondary structure requirement of the vRNA promoter for polymerase binding. Binding required a panhandle structure and the presence of local hairpin loop structures in both the 5' and 3' ends of vRNA, as suggested by the corkscrew model. The interaction of the vRNA promoter with the influenza virus RNA polymerase heterotrimeric complex is likely to favor a particular closed conformation of the complex, thereby ensuring the stability of the RNA polymerase within both the infected cell and the isolated virus.